MENINGKATKAN AKTIVITAS DAN KETERAMPILAN KERJA SAMA MENGGUNAKAN MODEL PEMBELAJARAN SOLID BERBANTUAN MEDIA AUDIO VISUAL PADA MUATAN IPAS KELAS IV SDN KUIN UTARA 5 BANJARMASIN - Khairati Olfah; Ratna Purwanti; Ahmad Suriansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The problem in this research is the low level of activity, collaboration skills and student learning outcomes. The causes are that learning is still one-way, the lack of use of supportive learning models and media, and the lack of group activities. The solution to overcome this problem is to apply the SOLID learning model, which is a combination of Project Based Learning (PjBL), Scramble, and Course Review Horay (CRH) with the help of audio-visual media. This research was conducted as classroom action research (PTK) over 4 meetings. The research subjects were fourth grade students at SDN Kuin Utara 5 Banjarmasin, consisting of 18 students in the 2023/2024 academic year. The data collected is qualitative and quantitative. Qualitative data is obtained from observing teacher and student activities, while quantitative data comes from collaboration skills and student learning outcomes. Data analysis was carried out using descriptive techniques and cross tabulation, which was explained through tables, graphs and percentage interpretation. The research results showed that the teacher's activity at meeting 1 received a score of 32 with "Good" criteria, and increased at meeting 4 to a score of 39 with "Very Good" criteria. Classical student activity at meeting 1 reached 61% with the criterion "Quite Active" and increased to 94% with the criterion "Very Active" at meeting 4. Student collaboration skills also increased from 61% (Quite Skilled) at meeting 1 to 94% (Very Skilled) at meeting 4. This increase had a positive effect on student learning outcomes, which showed an increase from meetings 1 to 4 with a classical completion level reaching 89%. From the research results, it can be concluded that the application of the SOLID learning model is effective in increasing activity, collaboration skills and student learning outcomes.